Helioseismology: The observations of low degree oscillations of the Sun from the South Pole to SoHO - Grec, Gérard (Известия Крымской астрофизической обсерватории, 2008)
Thanks to the pioneer works of F. Deubner, the G. Isaack group at Birmingham, and the observations made at the geographic South Pole by G. Grec, E. Fossat and M. Pomerantz, the “5 min” oscillations of the photosphere discovered earlier by R. Noyes and R. Leighton are understood as spherical modes of oscillation. At that time it was an analytic concept due to P. Ledoux, already applied to stellar oscillations; the asymptotic analysis due to M. Tassoul has been a surprising key to identify the solar acoustical modes.